Adverse Childhood Experiences and Resilience: Family Resilience as a Promotive Factor in Young Children’s Flourishing - Erica M. Thompson; Frederique Corcoran; Hopewell R. Hodges (SAGE Open)
There is a well documented connection between children’s exposure to adverse childhood events (ACEs) and the risk of negative outcomes. However, many children with ACE exposure go on to perform fairly well in life, due to the support from multiple interacting systems within and around them. Resilience science has led to the development of creative interventions and policies that prevent negative outcomes for children. There is growing attention, though, to the promotion of positive outcomes such as flourishing, which matters profoundly to individual and collective well-being. Flourishing has not been well examined in young people exposed to adversity, especially in early childhood. The objective of this work is to identify family-level mechanisms that support children’s flourishing amid adversity. It draws from a nationally representative sample of children from the United States under the age of six ( n  = 8,174) who were included in the National Survey of Children’s Health (NSCH). In addition to surveys on ACE exposure, the NSCH used a four-item index to measure children’s flourishing, which was operationalized as positive emotionality, relational health, and emotional resilience. Using structural equation modeling (SEM) with path analysis, this work found that exposure to ACEs was negatively and directly associated with children’s flourishing, but that children in families with higher family resilience showed higher levels of flourishing. Furthermore, there were indirect associations between ACEs and flourishing, where about 60% of the effect of ACEs on flourishing was mediated through family resilience. We offer program- and policy-level suggestions for enhancing young children’s flourishing through promotion of family resilience and prevention of ACEs.